The Importance of E-learning in teaching religious science courses at the secondary level from the perspective of female teachers - Almuawi, Sarah Saeed Jabbar (Journal of Educational and Psychological Sciences, 2021)
This study aimed to investigate the significance of E-learning in the teaching of religious science courses at the secondary level, and to examine the obstacles of employing it, from the perspective of female teachers in the Kingdom of Saudi Arabia. A descriptive method was used through distributing a questionnaire that composed of (26) statements divided into two main sections, in addition to an open ended question. The questionnaires were distributed over a random sample of (83) female teachers who teach the subjects of religious science for the secondary stage in the Riyadh region as the female teacher amount in this region could aid to reach an accurate study result. The results of the study showed that the significance of employing e-learning in teaching religious science courses to female teachers, was in a medium rate, with an average of (3.15) and a percentage (63%). Furthermore, the degree of the significance of employing e-learning to students was in the medium rate with an average of (3.48) with a percent of (69.6%). The results of the study also showed that teachers face several obstacles’ when utilizing e-learning in the teaching of religious science courses with a medium rate, with an average (3.44) and a percentage (68.8%). The obstacles focus on deficiencies in the Internet infrastructure and technological equipment in most schools, and the lack of adequate computers for all students, and the lack of knowledge among teachers regarding the e-learning methods and procedures. In addition to the fact that most teachers are not convinced of using e-learning in teaching religious science courses. The study also made proposals to enhance the level of employing e-learning, and the most significance suggestion is to improve the secondary schools infrastructure, and to ensure providing the necessary equipment and resources to implement e-learning for students, to enhance the level of knowledge of religious science teachers in dealing with modern technology, especially e-learning, and to allocate moral and material rewards for teachers who use e-learning effectively. The study recommended to pay attention to the preparation of specialized training programs and workshops for teachers of religious science in the field of e-learning in order to provide them with sufficient knowledge and technical skills to employ it in the educational process.